Columbo :The Complete First Season Disc 1 - Steven Spielberg; Colby, Barbara, 1940-; Bernie Kuby; Jack Cassidy; Lynette Mettey; Martin Milner; Rosemary Forsyth; Peter Falk (USA Universal Studios, 1971)
Ken Franklin is a rich socialite living in a luxurious coastal mansion bought from his years of writing crime and mystery books. However, what he once wrote as fiction becomes reality as he murders a man and then desperatly tries to cover up his crime when he is blackmailed by a witness. As usual, Columbo arrives on the scene and begins to pester his suspect with questions about the murder. Mr. Franklin soon realises though, that no murder is perfect, and that one of his books may return to haunt him.
Ken Franklin is a rich socialite living in a luxurious coastal mansion bought from his years of writing crime and mystery books...
Steven Bochco
Language: English Subtitle: English
Keywords: Drama; Mystery -- Tv Series; Crime